Common genetic variants associated with melanoma risk or naevus count in patients with wildtype MC1R melanoma. (11th August 2022) - Calbet‐Llopart, Neus; Combalia, Marc; Kiroglu, Anil; Potrony, Miriam; Tell‐Martí, Gemma; Combalia, Andrea; Brugues, Albert; Podlipnik, Sebastian; Carrera, Cristina; Puig, Susana; Malvehy, Josep; Puig‐Butillé, Joan Anton
Summary: Background: Hypomorphic MC1R variants are the most prevalent genetic determinants of melanoma risk in the white population. However, the genetic background of patients with wildtype (WT) MC1R melanoma is poorly studied. Objectives: To analyse the role of candidate common genetic variants on the melanoma risk and naevus count in Spanish patients with WT MC1R melanoma. Methods: We examined 753 individuals with WT MC1R from Spain (497 patients and 256 controls). We used OpenArray reverse‐transcriptase polymerase chain reaction to genotype a panel of 221 common genetic variants involved in melanoma, naevogenesis, hormonal pathways and proinflammatory pathways. Genetic models were tested using multivariate logistic regression models. Nonparametric multifactor dimensionality reduction (MDR) was used to detect gene–gene interactions within each biological subgroup of variants. Results: We found that variant rs12913832 in the HERC2 gene, which is associated with blue eye colour, increased melanoma risk in individuals with WT MC1R [odds ratio (OR) 1·97, 95% confidence interval (CI) 1·48–2·63; adjusted P < 0·001; corrected P < 0·001]. We also observed a trend between the rs3798577 variant in the oestrogen receptor alpha gene ( ESR1 ) and a lower naevus count, which was restricted to female patients with WT MC1R (OR 0·51, 95% CI 0·33–0·79; adjusted P = 0·002; corrected P = 0·11). This sex‐dependent association was statistically significant in a larger cohort of patients with melanoma regardless of their MC1R status ( n = 1497; OR 0·71, 95% CI 0·57–0·88; adjusted P = 0·002), reinforcing the hypothesis of an association between hormonal pathways and susceptibility to melanocytic proliferation. Last, the MDR analysis revealed four genetic combinations associated with melanoma risk or naevus count in patients with WT MC1R . Conclusions: Our data suggest that epistatic interaction among common variants related to melanocyte biology or proinflammatory pathways might influence melanocytic proliferation in individuals with WT MC1R . What is already known about this topic? Genetic variants in the MC1R gene are the most prevalent melanoma genetic risk factor in the white population. Still, 20–40% of cases of melanoma occur in individuals with wildtype MC1R . Multiple genetic variants have a pleiotropic effect in melanoma and naevogenesis. Additional variants in unexplored pathways might also have a role in melanocytic proliferation in these patients. Epidemiological evidence suggests an association of melanocytic proliferation with hormonal pathways and proinflammatory pathways. What does this study add? Variant rs12913832 in the HERC2 gene, which is associated with blue eye colour, increases the melanoma risk in individuals with wildtype MC1R . Variant rs3798577 in the oestrogen receptor gene is associated with naevus count regardless of the MC1R status in female patients with melanoma. We report epistatic interactions among common genetic variants with a role in modulating the risk of melanoma or the number of naevi in individuals with wildtype MC1R . What is the translational message? We report a potential role of hormonal signalling pathways in melanocytic proliferation, providing a basis for better understanding of sex‐based differences observed at the epidemiological level. We show that gene–gene interactions among common genetic variants might be responsible for an increased risk for melanoma development in individuals with a low‐risk phenotype, such as darkly pigmented hair and skin. Abstract : We evaluated 2221 candidate common genetic variants in individuals with WT MC1R from Spain. We observed that the rs12913832 HERC2 variant increases the melanoma risk in these individuals and that the rs3798577 ESR1 variant might be associated with the naevus count in female melanoma patients regardless of their MC1R status. Our data also suggest that epistasis among genetic variants related to melanocyte biology or pro‐inflammatory pathways might play a role in melanoma susceptibility or naevus count determination in individuals with WT MC1R .